2020
DOI: 10.1044/2019_jslhr-19-00152
|View full text |Cite
|
Sign up to set email alerts
|

Development of Phonetic Contrasts in Cantonese Tone Acquisition

Abstract: Purpose Previous studies showed both early and late acquisition of Cantonese tones based on transcription data using different criteria, but very little acoustic data were reported. Our study examined Cantonese tone acquisition using both transcription and acoustic data, illustrating the early and protracted aspects of Cantonese tone acquisition. Method One hundred fifty-nine Cantonese-speaking children aged between 2;1 and 6;0 (years;months) and 10 ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, for the acoustic comparison of the rising tonal pair in Cantonese (CT23 vs. CT25), they additionally show a covert contrast at the temporal distinction of "inflection point". The minimum F0 value appears slightly earlier in the high-rising CT25 compared to that in low-rising CT23 along the pitch contour (Mok et al, 2020).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, for the acoustic comparison of the rising tonal pair in Cantonese (CT23 vs. CT25), they additionally show a covert contrast at the temporal distinction of "inflection point". The minimum F0 value appears slightly earlier in the high-rising CT25 compared to that in low-rising CT23 along the pitch contour (Mok et al, 2020).…”
mentioning
confidence: 83%
“…Only a main effect of language on the linear term (pitch slope) of level tones was found, with Cantonese-speaking children eliciting a more falling F0 slope compared to Mandarin-speaking ones. It was reported that Cantonese speakers tended to produce a slightly falling contour in their actual realization of three level tones, especially for the low-level and mid-level tones (Mok et al, 2020;Zhang et al, 2018). Thus, the cross-linguistic differences in the acoustic realization of level tones could be attributed to the influence of long-term native language experience.…”
Section: Speech-specific and Contour-biased Lexical Tone Processing A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the previous and present findings support PAM-S in the context of native English listeners and Cantonese heritage children in an English-speaking country. Like the previous study (Kan & Schmid, 2019), our hypothesized assimilation patterns were based on (1) the acoustic similarities between tones and intonations and (2) previous empirical findings (Francis et al, 2008; Mok et al, 2020). Although our discrimination results clearly supported the hypothesized assimilation patterns, ideally, an assimilation task would have strengthened our assimilation claims.…”
Section: Discussionmentioning
confidence: 95%
“…PAM-S yields several predictions for English listeners' Cantonese tone discrimination. Acoustically, a falling tone resembles a statement intonation, whereas a rising tone resembles a question intonation (Ladefoged, 2006;Mok et al, 2020). Compared with a falling tone, a level tone resembles a statement intonation less.…”
Section: Pam For Suprasegmentalsmentioning
confidence: 99%